Studies on Philanthropy and Impact Investment in Ghana - Osei, Dennis Boahene (University of the Witwatersrand, Johannesburg, 2021)
Anecdotal evidence of practices and institutions has accumulated over the years through oral traditions and all over the psyche of the African. While giving to good causes is not new in the Ghanaian traditional system and culture, there is a general paucity of literature regarding recent developments on the topic. Studies regarding investments that simultaneously generate financial, as well as social and /or environmental returns, are equally lacking. Using Ghana as a case study, this thesis contributes to the literature on three thematic areas in accordance with identified gaps in the philanthropy and impact investment literature. Specifically, the thesis relies on quantitative (instrumental variable probit model) and qualitative (content analysis, multiple-case study) research techniques to examine the relationships, and determinants of formal and informal charitable giving; uncover the motives, priorities, strategies, opportunities, and challenges of corporate foundation giving; and explore the approach to impact investing. These are critical issues whose understanding is theoretical and western-oriented, lacking empirical attention in the emerging literature of African philanthropy and impact investment. Given this, the thesis produced three independent essays to address these salient gaps in the philanthropy and impact investment literature. Empirical findings evolving from these essays are instructive and generally present crucial insights on African philanthropy and impact investment which is relevant for policy and practice. The first essay examines the extrinsic (socio-demographic) and intrinsic (personality) determinants of both formal and informal charitable giving. In addition, it explores whether the relationship between different types of charitable giving –cash and in-kind donations as well as time donations (volunteering) – is substitutable or complementary. Our findings, based on survey data from 1,533 households and instrumental variable probit model revealed that while marital status, education, household size, religiosity, ethnicity, and empathic concern are important predictors of formal cash and in-kind giving, informal giving of cash and in-kind is driven by income, religiosity and empathic concern. On the other hand, it was evident that formal volunteering is mainly determined by income, household size, religiosity, and empathic concern, whereas gender and religiosity influence informal volunteering. We established that, in both spheres of formal and informal giving, the relationship between cash and in-kind giving and volunteering is complementary. Premised on these findings, we recommend non-profits and policymakers to recognise the complementary role and distinctive determinants of the spheres of giving in designing tools and policies to raise the levels and effectiveness of fundraising and volunteering campaigns. In the second essay, the practice of corporate philanthropy was explored through the lens of corporate foundations. Specifically, we investigate the motives, priority areas, strategies, opportunities, and challenges of corporate foundation giving. Based on qualitative content analysis, our findings revealed that corporate foundations are influenced by both altruistic and instrumental motives of giving, and that, their approach to giving prioritises multiple areas of national interest such as education, health, economic empowerment, environment/social amenities, and sports. We also found that corporate foundations rely on a combination of strategies (request, media-lead, adoption, and contest) to identify potential beneficiaries and implement their giving programmes. Further evidence indicates that giving of corporate foundations presents opportunities to both foundations (serve society, get partnership offers from other companies, and obtain goodwill from the public) and their parent companies (indirect business and advertising opportunities). However, corporate foundation giving is constrained by insufficient funding, lack of support from stakeholders, managing expectations of individuals, poor maintenance culture, and cultural rites. The findings have implications for practitioners as it presents insights which could serve as a model to guide new entrants into the corporate foundation landscape of developing economies. In addition, the findings could assist the development of government interventions necessary to foster greater corporate giving. The third essay applies a change in perspective to explore the approach to impact investing from a supply-side standpoint. This contrasts existing studies which are mostly theoretical and provide an understanding that is western-oriented and from a demand-side viewpoint. Using multiple-case study design and qualitative data from two Ghanaian organisations, we provide evidence of an impact investment approach characterised by concurrent motive of financial and social/environmental returns, longer time horizon, and engagement or provision of non-financial support. We conclude that this approach leverages the tools of venture capital to realise social or ecological purposes. The findings can potentially assist investors and entrepreneurs to make informed decisions and navigate the complexity surrounding the emerging impact investment environment in Ghana and economies of similar nature. Additionally, it can help in developing explicit policies to regulate the sector, increase its awareness, widens its appeal, and use to serve the intended purpose of addressing social and environmental problems
Doctoral thesis submitted in fulfillment of the requirements for the award of the degree of Doctor of Philosophy The Graduate School of Business Administration, Wits Business School University of the Witwatersrand, Johannesburg 2021
Keywords: Giving; Volunteering; Corporate Philanthropy and Foundations; Impact and Social Investments; SMEs; Ghana; UCTD; SDG-8: Decent work and economic growth